Management of Locally Advanced Renal Cell Carcinoma - Vsevolod B. Matveev; Sarah P. Psutka; Grant D. Stewart; Gennady Bratslavsky; E. Jason Abel (Société Internationale d’Urologie Journal)
Renal cell carcinoma (RCC) has a natural tendency to invade the venous system with formation of a venous tumor thrombus in the renal vein, which can extend proximally into the inferior vena cava (IVC) and in some cases into the right atrium. The presence of venous involvement significantly worsens prognosis. Despite recent advances in systemic therapies, surgery remains the most effective method of treatment and in the case of complete removal of all tumor, it provides satisfactory long-term survival and must be attempted whenever possible. Several surgical techniques have been proposed, but all are associated with a high rate of perioperative complications and mortality. Minimally invasive approaches are mainly applicable for less extended IVC thrombi, while open surgery remains the gold standard for this category of patients. Most IVC thrombi can be managed without use of circulatory support by using different methods of IVC control depending on the thrombus level. However, use of cardiac bypass with or without deep hypothermic cardiac arrest is indicated in some patients with bulky intraatrial tumor thombi. In select patients presenting with IVC tumor thrombus and synchronous distant metastases, cytoreductive nephrectomy with IVC tumor thrombectomy may be considered with or without neoadjuvant systemic therapy. Surgery for RCC with venous thrombus is complex and requires experienced multidisciplinary surgical, anesthesia, and critical care teams at high-volume centers to achieve the best outcomes.